First record of an abelisaurid (Dinosauria, Theropoda) natural endocast, and comments on skull roof ornamentation - Paulina Carabajal, Ariana (2023)
We present here a natural cranial endocast assigned to an abelisaurid theropod found in Cretaceous rocks of the outcropping Bajo de la Carpa Formation (Santonian) in Neuquén Province, Northern Patagonia, Argentina. The specimen was found in association with fragmentary braincase remains, which include an otic capsule and part of the skull roof. These fragments bear abelisaurid features that support the taxonomic assignment. The general shape of the endocast is similar to that in other abelisaurids, being anteroposteriorly elongated with long and robust olfactory tract and olfactory bulbs, rounded cerebralhemispheres, and pronounced and triangular dural peak. It is the second natural endocast described for a dinosaur in Argentina and the first for a theropod. The comparison with other Patagonian abelisaurids indicates the endocast belonged to a small to mid-sized specimen that highly resembles that of Viavenator and Llukalkan. However, the skull roof ornamentation is markedly different, and comments are made on certain features of the ornamentation of the frontal in the new specimen and other close relatives.